Etymology of the Term “Dusun” from Literature Perspectives of Old Written Record - Jude James; Rosy Talin; Soon Singh Bikar Singh (Universiti Malaysia Sarawak, 2022)
For a long time, the term "Dusun" has captivated our curiosity. Its origin is unmistakably an exonym. However, few people have written about it, synthesized it, or can explain it in depth. Thanks to advances in information technology, now it is possible to assemble documents or record about historical Borneo from diverse sources around the world. The tasks of collecting historical materials from the colonial of a bygone era has become easier. Due to this, it is a good time to explore a fresh perspective on the historical phases of this ethnic category. To describe the evolution of the phrase, the study includes explorers' journals, semi autobiographies, historical sources, and other written scientific studies.